2017
DOI: 10.1111/jgs.14784
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and 25‐Hydroxyvitamin D Blood Level Response to Vitamin D Treatment of Older Adults

Abstract: Of persons aged 60 and older at high risk of vitamin D deficiency, statin users had a 21.4% smaller increase in 25(OH)D serum concentrations over time than nonusers, independent of vitamin D dose and other covariates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(69 reference statements)
0
10
0
1
Order By: Relevance
“…Since dietary vitamin D intake from food and supplements is the main determinant of vitamin D status in older adults, increased 25(OH)D levels among statin users were particularly seen among those with inadequate vitamin D intake [21]. In addition, Bischoff-Ferrari et al in a pooled analysis of three double-blind randomized clinical trials suggested that lower 25(OH)D response to vitamin D supplementation may be a class effect of all statins, which differ according to vitamin D dosing regimens [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since dietary vitamin D intake from food and supplements is the main determinant of vitamin D status in older adults, increased 25(OH)D levels among statin users were particularly seen among those with inadequate vitamin D intake [21]. In addition, Bischoff-Ferrari et al in a pooled analysis of three double-blind randomized clinical trials suggested that lower 25(OH)D response to vitamin D supplementation may be a class effect of all statins, which differ according to vitamin D dosing regimens [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, few observational studies and randomized controlled trials reported conflicting results regarding the effect of statins on 25(OH)D concentrations. Some studies described higher 25(OH)D concentrations among statin users, whereas others did not [7][8][9][10][11][12][13][14][15]. Nevertheless, these studies were limited by small sample size, subjects with acute coronary syndrome, individual generic statins, diabetics hospitalized, and postmenopausal women with osteopenia [7,9,11,[14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous medications can lead to low bone mineral density and an increased risk for fracture. Statins may cause a decline in vitamin D levels and lead to smaller increases in serum 25(OH)D concentration even with supplementation [ 18 , 19 ]. Anticonvulsant medications accelerate vitamin D metabolism and increase the risk for fracture [ 65 ].…”
Section: Life In the Margins: The Health Impact Of Micronutrient Insumentioning
confidence: 99%
“…[58] Only one study claimed that statin decreased vitamin D levels by 21.4% in patients aged 60 and older. [59] So far, evidence regarding the association of statin and vitamin D has remained inconclusive due limited data and conflicting results. Further randomized controlled trials are warranted to make a direct correlation.…”
Section: Cholesterol Statin and Brain Diseasementioning
confidence: 99%